Web-Based Bangun Jaya Workshop Information System - Djauhari, Teuku; Huda Aminuddin, Fattachul; Gwandy Rianto, Muhammad; Rahmawati, Noni; Husna Ahadi, Ahmad (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Bangun Jaya Workshop is a business in the field of car service or repair. Bangun Jaya Workshop serves painting and engine repair, buying and selling used two-wheeled vehicles and motorbikes at the Bangun Jaya Workshop. Currently, if you want to repair your car, customers are required to complete the payment administration data via transfer. Current information technology allows people to communicate in multiple directions without having obstacles of distance, place and time. The role of the information technology system also greatly supports data processing in a company, organization, institution or agency with the intention of making it easier to obtain relevant, accurate and timely information. The purpose of the research is to produce a website- based workshop information system to improve the quality of workshop services to customers so that they can order service online. The input requirements for this system are admin data, customer data, company profile data, car and motorbike spare part sales data and used motorbike sales data and motorbike and car spare part service data. The process requirements for this system are the login process to the system, the consumer data processing process, the motorbike and car spare part data processing process, the incoming goods data processing process, the outgoing goods data processing process and the service transaction data processing process and the motorbike and car service data processing process. The output needs are information on spare part data reports and information on incoming goods data as well as information on motorcycle and car service data reports.